Chloroplast Acetyltransferase GNAT2 is Involved in the Organization and Dynamics of Thylakoid Structure. (6th July 2022) - Rantala, Marjaana; Ivanauskaite, Aiste; Laihonen, Laura; Kanna, Sai Divya; Ughy, Bettina; Mulo, Paula
Abstract: Higher plants acclimate to changes in light conditions by adjusting the thylakoid membrane ultrastructure. Additionally, excitation energy transfer between photosystem II (PSII) and photosystem I (PSI) is balanced in a process known as state transition. These modifications are mediated by reversible phosphorylation of Lhcb1 and Lhcb2 proteins in different pools of light-harvesting complex (LHCII) trimers. Our recent study demonstrated that chloroplast acetyltransferase NUCLEAR SHUTTLE INTERACTING (NSI)/GNAT2 (general control non-repressible 5 (GCN5)-related N-acetyltransferase 2) is also needed for the regulation of light harvesting, evidenced by the inability of the gnat2 mutant to perform state transitions although there are no defects in LHCII phosphorylation. Here, we show that despite contrasting phosphorylation states of LHCII, grana packing in the gnat2 and state transition 7 (stn7) mutants possesses similar features, as the thylakoid structure of the mutants does not respond to the shift from darkness to light, which is in striking contrast to wild type (Wt). Circular dichroism and native polyacrylamide gel electrophoresis analyses further revealed that the thylakoid protein complex organization of gnat2 and stn7 resembles each other, but differ from that of Wt. Also, the location of the phosphorylated Lhcb2 as well as the LHCII antenna within the thylakoid network in gnat2 mutant is different from that of Wt. In gnat2, the LHCII antenna remains largely in grana stacks, where the phosphorylated Lhcb2 is found in all LHCII trimer pools, including those associated with PSII. These results indicate that in addition to phosphorylation-mediated regulation through STN7, the GNAT2 enzyme is involved in the organization and dynamics of thylakoid structure, probably through the regulation of chloroplast protein acetylation.